Conjure wife. - Leiber, Fritz, 1910-1992. (New York, Twayne Publishers, 1953)
Professor Norman Saylor considered magic nothing more than superstition. Then he learned that his own wife was a practicing sorceress. But he still refuses to accept the truth$1! =(Bthat in the secret occult warfare that governs our lives, magic is a matter of life and death. And that unbeknownst to men, every woman knows it.s
Keywords: Supernatural